MO755: Comparison of Techniques for Fluid Status Assessment in Chronic Hemodialysis Patients. (3rd May 2022) - Ekart, Robert; Piko, Nejc; Vodošek Hojs, Nina; Jakopin, Eva; Bevc, Sebastjan; Hojs, Radovan
Abstract: BACKGROUND AND AIMS: Several methods have been developed to assess hydration status in chronic haemodialysis (HD) patients. The aim of this study was to compare multifrequency body bioimpedance spectroscopy (MBIS) with ultrasound lung comet scores (ULCs) and inferior vena cava diameters (IVCD) using ultrasound to estimate dry weight on the non-dialysis day. METHOD: We evaluated MBIS, ULCs at 28 typical sites and IVCD during expiration in 40 HD patients. All measurements were performed on a non-dialysis day. For MBIS measurement, we used the Body Composition Monitor (Fresenius Medical Care, Bad Homburg, Germany), and for ULCs and IVCD, we used an ultrasound device (Esaote MyLabOmega, Genoa, Italy). Overhydration was defined as > 2L with MBIS, > 15 ULCs, and > 11.5 mm/m 2 IVCD. RESULTS: Mean age of patients was 65 (40–89) years, and 29 (72.5%) were men. Other descriptive data are in Table 1 . We found a significant correlation between MBIS and ULCs ( r = 0.464, P <0.003) and between MBIS and IVCD ( r = 0.589, P <0.001). Multiple regression analysis with the MBIS as the dependent variable and ULCs, IVCD, albumin and haemoglobin as independent variables confirmed a statistically significant relationship between MBIS and IVCD (β = 0.436; P < 0.001). According to the overhydration criteria, 14 (35%) patients were overhydrated by MBIS, 8 (20%) patients by ULCs and 9 (22.5%) patients by IVCD. Only 4 (10%) patients met overhydration criteria simultaneously by all three methods (MBIS, ULCs and IVCD). CONCLUSION: All methods were able to describe overhydration in HD patients on a non-dialysis day. The MBIS was associated with the IVCD.